Co-producing cyber protest: mesomobilization in the digital age. Issue 1 (2nd January 2018) - Odou, Philippe; Roberts, Graham H.; Roux, Dominique
ABSTRACT: This article examines how mesomobilization deploys on the web to foster online resistance. We focus on a particular cyber protest targeting a governmental campaign against illegal downloading and show how webzines, as meso-level actors, managed to turn their readers' comments into appealing frames around cultural legitimacy, Internet freedom and morality. In this instance, web users initiated the diagnostic framing and provided webzines with motives to launch a call to arms. This took the form of parody that produced a disruption and a set of grievances against the official campaign. Our fieldwork reveals the existence of online dormant networks – pre-existing fluid cultural groups sharing common interests – that meso-level actors readily mobilize when a crisis arises. Our study extends our understanding of consumer resistance by highlighting the dynamics of online networks in organizing overt protest and political challenge.